Statistical Analysis of the Occurrence of Ionospheric Scintillations at the Low-Latitude Sanya Station During 2004–2021 - Bo Xiong; Changhao Yu; Xiaolin Li; Yuxiao Li; Lianhuan Hu; Yuqing Wang; Lingxiao Du; Yuxin Wang (Remote Sensing)
The ionosphere of the Earth often becomes turbulent and develops electron density irregularities that can cause rapid and random changes in the amplitude and phase of radio signals, which is known as ionospheric scintillation. In this study, the statistical behavior of global navigation satellite system (GNSS) ionospheric amplitude scintillation of varying intensities over the Chinese low-latitude station in Sanya (18.34°N, 109.62°E; magnetic latitude: 7.61°N) has been investigated with respect to its dependence on solar activity, seasons, local time (LT), and geomagnetic activity during the period from July 2004 to December 2021. A detailed study on the solar activity dependence of scintillation occurrence shows that the occurrence rates of strong and moderate scintillations significantly increase with enhanced solar activity, but weak amplitude scintillations do not entirely conform to this characteristic. In terms of seasonal dependence, the scintillations in Sanya from 2004 to 2021 mainly occurred during equinoxes and exhibit a distinct equinoctial asymmetry. This asymmetry is characterized by a higher occurrence rate in autumn than in spring during the years 2007, 2011, and from 2017 to 2021, while in other years, the pattern is reversed, with a higher occurrence rate in spring than in autumn. Regarding LT dependence, scintillations are predominantly observed during 19:30–23:30 LT, with a notable persistence beyond midnight during years of high solar activity. Furthermore, geomagnetic disturbances have been observed to promote weak scintillations at 20:00 LT during the autumn and winter of 2014, and from 20:00 LT to 01:00 LT the next day in the latter half of 2013. In contrast, during the spring and autumn of most other years with high solar activity, these disturbances have been found to inhibit weak scintillations from 20:00 LT to midnight. The promoting/inhibiting effect of geomagnetic disturbances on ionospheric scintillation is not solely influenced by electric field disturbances but is to some extent jointly controlled by a variety of factors including solar activity, season, and LT.